This Isn’t Just a Phantom, Menopause, But You Can Vent Your Feelings - Qualitative Evaluation of Evidence Based Health Information (EBHI) Material - B Berger; K Boehm (Journal of Women's Reproductive Health, 2017)
Objective Because of the increased demand for the availability of independent information regarding the efficacy, the lack of efficacy and the possible harm of medical interventions, the study aims to evaluate the information package „Menopause
Keywords: Evidence-based health information (EBHI)